Development of ready-to-drink (RTD) sweet potato leaf extract (SPLE) in glass bottles - Angluben, Gabriella L.
The study aimed to optimize the formulation parameters i.e. calamansi-honey concentrate (CHC) level (mL/ 100 mL sweet potato leaf extract) and process parameters i.e. processing time (PT) (min) for ready-to-drink (RTD) sweet potato leaf extract (SPLE) in glass bottle using central composite face-centered response surface methodology (RSM). The sweet potato leaf variety (i.e. Inubi and Kinerots), maturity (i.e. 1.5 months and 3 months) and sweetener used (i.e. CHC) were initially selected. The RSM models showed that CHC levels had significant (p<0.05) quadratic effects on both physicochemical properties (i.e. pH) and consumer acceptability (i.e. overall acceptability) whereas an interaction effect (CHC×PT) only had a significant (p<0.05) effect on the overall acceptability of the RTD SPLE in glass bottles. Results showed that the optimal combinations of: (1) young Inubi (CHC: 11.252 - 10.344 mL/ 100mL SPLE, PT: 2 min); (2) young Kinerots (CHC: 9.935 - 10.423 mL/ 100mL SPLE, PT: 2 min); (3) mature Inubi (CHC: 9.044 - 10.293 mL/ 100mL SPLE, PT: 2 min); and (4) mature Kinerots (CHC: 10.512 - 10.293 mL/ 100mL SPLE, PT: 2 min) produced a beverage with desirable range of pH and overall acceptability. Verification runs confirmed the predictive capacity and accuracy of the statistical models when predicting responses. This study, therefore, showed the potential of sweet potato leaves in the production of an RTD beverage.